Bounding the effect of a dichotomous regressor with arbitrary measurement errors - Deng, Ping; Hu, Yingyao (Economics letters, 2009)
This note considers a nonlinear regression model containing a 0–1 dichotomous regressor when it is subject to arbitrary measurement errors in the sample. The key identification assumption requires that the third conditional moment of the regression error is zero. This note suggests that the effect of the latent dichotomous variable may be bounded away from zero using the observed moments.